2004
DOI: 10.1007/s00787-004-0356-4
|View full text |Cite
|
Sign up to set email alerts
|

The Strengths and Difficulties Self-Report Questionnaire as a screening instrument in Norwegian community samples

Abstract: This study reports on the application of the Norwegian self-report version of the Strengths and Difficulties Questionnaire (SDQ-S). The application of the SDQ-S was not motivated by a wish to reveal the prevalence of psychiatric disorders, but rather to set the stage for routine screening as part of schools' efforts to inform themselves about the life of adolescents at school. The survey included 4167 young people aged 11 to 16 years, attending 66 primary and secondary schools in Northern Norway. The responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
156
5
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(193 citation statements)
references
References 12 publications
24
156
5
8
Order By: Relevance
“…Moreover, on the youth SDQ the CFI index never achieved acceptable values and two item loadings were unacceptably low. These findings therefore add to the CFA evidence that the SDQ does not have a very clean internal factor structure (Mellor & Stokes, 2007) but that the hypothesised five subscales may nonetheless provide a passable description (Ronning, et al, 2004;Ruchkin, et al, 2007;Van Leeuwen, et al, 2006).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Moreover, on the youth SDQ the CFI index never achieved acceptable values and two item loadings were unacceptably low. These findings therefore add to the CFA evidence that the SDQ does not have a very clean internal factor structure (Mellor & Stokes, 2007) but that the hypothesised five subscales may nonetheless provide a passable description (Ronning, et al, 2004;Ruchkin, et al, 2007;Van Leeuwen, et al, 2006).…”
Section: Discussionsupporting
confidence: 51%
“…Those CFAs which have been carried out provide at best mixed support for the SDQs five-factor structure. CFAs in Norway (youth SDQ) and Australia (parent, teacher and youth SDQ) found that models based on the hypothesised five factors did not show acceptable model fit for some or all indices considered (Mellor & Stokes, 2007;Ronning, Handegaard, Sourander, & Morch, 2004). Other CFAs in Belgium (parent and teacher SDQ) and Russia (youth SDQ) do report adequate global fit, but also note that loadings on several items were unacceptably low (<0.4) (Ruchkin, Koposov, & Schwab-Stone, 2007;Van Leeuwen, Meerschaert, Bosmans, De Medts, & Braet, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Given that no previous psychometric evaluation of the SDQ has taken place in South Africa, the current study therefore aimed to: (i) examine the means, standard deviation, distribution and internal consistency of the SDQ-S in a representative sample of adolescent boys and girls; (ii) compare gender differences in the above psychometric properties; (iii) determine the proportion of boys and girls who scored in the 'normal', 'borderline' and 'abnormal range' of SDQ-S subscales based on UK norms, and, if required, to generate South African cut-off scores; (iv) compare mean SDQ-S scores of the South African sample to previously reported normative data for SDQ-S scores in UK, Australian and Chinese samples; and (v) determine whether the South African SDQ-S data would fit the five-factor structure of the original UK SDQ-S. We hypothesised that significant differences on the basis of gender will exist in SDQ-S scores as found in previous studies (Becker et al 2015;Kremer et al 2015), hypothesised that South African cut-off scores may be required, as reported in other studies from LMICs (Kashala et al 2005;Menon et al 2007;Bakare et al 2010;Cortina et al 2013), and that there would be only partial support for the five-factor structure, as reported elsewhere (Rønning et al 2004;Richter et al 2011;Stevanovic et al 2014). We did not hypothesise any specific patterns of similarities or differences between the South African, UK, Australian and Chinese data, but were keen to explore the crosscountry potential of the instrument.…”
Section: Introductionmentioning
confidence: 81%
“…Nevertheless, several studies have detected low values of reliability (Cronbachs's alpha ˂ .60), especially in the Conduct problems and Peer problems subscales [16][17][18][19][20][21][22][23]11,24,25]. An added value of the test, as it the fact that it contains positive items, could be a key factor in explaining low internal consistency and the inconsistency of factorial solutions [26].…”
mentioning
confidence: 99%